Decision framework for the environmental management of explosive contaminated land - Ladyman, Melissa K.; Temple, Tracey; Piperakis, Michael; Fawcett-Hirst, William; Gutierrez-Carazo, Encina; Coulon, Frederic (Elsevier, 2019)
The environmental risks from explosive manufacturing and testing activities are usually evaluated using a qualitative process such as environmental impact prioritisation as recommended by legislation and guidance. However, standard environmental management system (EMS) guidance rarely provides detailed information on how to objectively assess the significance of the environmental impacts based on a rational scientific evidence. Quantitative exposure and eco-toxicity assessments are frequently used in combination with environmental threshold limit guidelines, but these omit important environmental impacts such as physical damage to land, nuisance and contribution to climate change. These impacts are particularly relevant to the explosives industry where noise nuisance and physical damage are given high priority. In addition, contamination from explosive compositions may comprise mixtures of multiple legacy and new generation explosives such as 1,3,5-trinitro-1,3,5-triazinane (RDX), 2,4,6-trinitrotoluene (TNT), 5-nitro-1,2,4-triazol-3-one (NTO), 2,4-dinitroanisole (DNAN) and nitroguandine (NQ), which may have combined impacts not captured by conventional eco-toxicity assessments. Further, threshold limits for energetic materials in soil and water have not been established for most nations. Additionally, in the explosive industry wider concerns such as legislative compliance and stakeholder concerns may help to provide a more broadly applicable assessment of environmental impact. Therefore in this study a novel decision framework was developed to integrate empirical data with business risks to enable rational decision making for the environmental management of explosive manufacturing facilities. The application of the framework was illustrated using three case studies from the explosive manufacturing industry to demonstrate how the framework can be used to justify environmental management decision making. By linking the environmental impacts to business risks, we demonstrate that manufacturers are able to assess a wide spectrum of issues that might not be identified in the initial environmental assessment such as non-toxic pollution incidents, breaches in legislation and stakeholder perceptions.
Keywords: Environmental impact assessment; Business risk; Soil contamination; Water contamination; Air pollution